Increased stiffness of median nerve in systemic sclerosis - YAĞCI, İLKER; KENİŞ COŞKUN, ÖZGE; DİRESKENELİ, RAFİ HANER (BIOMED CENTRAL LTD, 2017)
Background: Systemic sclerosis can affect peripheral nerves, but the extent and the nature of this involvement are not well defined. The aim of this study is to compare the sonoelastrographic measurements of median nerves in systemic sclerosis (SSC), idiopathic carpal tunnel syndrome (CTS) and healthy individuals. Methods: The clinical, electrophysiological and ultrasonographic assessments were done. Patients with SSC and CTS were assessed with nerve conduction studies. The measurements of cross sectional areas (CSA) were performed at psiform and forearm level from axial US images. The elastic ratio is the ratio of strain distribution in two selected region of interests (ROI) done via comparing the median nerve to flexor digitorum superfcialis tendon. The ROIs were fixed to 2 mm. Results: The study was completed with 47 hands of 24 patients with SSC, 53 hands of 27 patients with CTS and 38 hands of health controls. The CSA of CTS group was significantly higher than systemic sclerosis and control groups. The elastic ratio at psiform level and forearm levels of systemic sclerosis group were significantly higher than the CTS and control groups. Conclusion: Median nerves lose the elasticity while the CSA's are in the normal range in patients with SSC. These results suggested that the increased peripheral nerve involvement in SSC is about the increased stiffness of the nerves.
Keywords: Carpal tunnel syndrome; Median nerve; Sonoelastography; Systemic sclerosis; CARPAL-TUNNEL-SYNDROME; ULTRASOUND ELASTOGRAPHIC EVALUATION; PERIPHERAL NEUROPATHY; INVOLVEMENT; SCLERODERMA; DIAGNOSIS